2015
DOI: 10.1007/s10943-015-0160-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Self-Perceived Changes in Gastrointestinal Symptoms During Ramadan Fasting

Abstract: Little is known regarding the effects of Ramadan fasting on common gastrointestinal symptoms. The aim of this study was to assess the alterations of these symptoms in a healthy Iranian adult population during Ramadan. In a cross-sectional study, self-administered questionnaires were used to evaluate the alterations in seven groups of gastrointestinal symptoms (esophageal symptoms, dyspeptic symptoms, bloating and abdominal distension, constipation, diarrhea, abdominal pain, and nausea) after Ramadan. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…In this study, the increased intake of dietary fibers, vitamin C, beta-carotene, and vitamin A (expressed as retinol equivalent) during Ramadan compared to the non-fasting remainder of the year could be explained by a higher intake of vegetables, and dried fruit during Ramadan night hours. This increased intake of fiber-rich foods could be looked at as a prophylactic measure for the anticipated and frequently experienced constipation during the fasting hours, which is exaggerated with the lack of water intake and reduced physical activity during Ramadan (68). Besides, fresh and dried fruits and vegetable salads are principal ingredients in many dishes during and out of Ramadan in the traditional Lebanese cuisine, which is part of the Mediterranean diet pattern (42).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the increased intake of dietary fibers, vitamin C, beta-carotene, and vitamin A (expressed as retinol equivalent) during Ramadan compared to the non-fasting remainder of the year could be explained by a higher intake of vegetables, and dried fruit during Ramadan night hours. This increased intake of fiber-rich foods could be looked at as a prophylactic measure for the anticipated and frequently experienced constipation during the fasting hours, which is exaggerated with the lack of water intake and reduced physical activity during Ramadan (68). Besides, fresh and dried fruits and vegetable salads are principal ingredients in many dishes during and out of Ramadan in the traditional Lebanese cuisine, which is part of the Mediterranean diet pattern (42).…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][97][98][99] Studies have indicated that patients with disrupted circadian rhythms present with gastrointestinal symptoms/ disorders, most notably constipation, and IBS. [48][49][50]53,62 Some studies of circadian rhythms in the gastrointestinal system have been hampered by the inability to adequately control external cues, such as light-dark cycles or food intake in many clinical studies. 77 Nevertheless, constipation has been associated with circadian rhythm-dependant differences in colonic transit following waking or food consumption, and frequency of bowel movements compared to nonconstipated patients.…”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire measured the rate of constipation in 900 individuals and found that those who fasted for > 14 days reported more "severe" or "very severe" constipation than those who fasted for <14 days. 62 However, alimentation is a confounding factor, affected by the increased volume of food intake and, in some cases, the introduction of traditional dishes. 24,25 There are conflicting reports on MMC duration, ie, shorter vs. no difference 37,38 Colon Normal colonic motility follows a circadian rhythm, with minimal activity during the night and increased activity during the day HAPCs are more prevalent in the morning 36 LAPCs increase after meals and during the day 10 Antegrade propagating sequences are more frequent and of greater amplitude during daytime hours 39 Retrograde propagation sequences are less frequent and have lower amplitude during daytime hours 42 Postprandial distal colonic activity consists primarily of retrograde propagating sequences following a meal in healthy persons 43…”
Section: Constipationmentioning
confidence: 99%
“…Likewise, a recent systematic review of interventions studying the effect of high fiber cereal on bowel function indicated that wheat fiber promotes healthy bowel function as it improves total stool weight, dry stool weight, intestinal transit time, and stool frequency [38]. In addition, other studies conducted on Ramadan fasting individuals reported constipation as the most frequent gastrointestinal symptom experienced by the end of Ramadan [39,40]. Therefore, recommending high fiber cereal to reduce symptoms of constipation and improve bowel function for fasting individuals during Ramadan should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%